2011
DOI: 10.1007/s10549-011-1914-3
|View full text |Cite
|
Sign up to set email alerts
|

Pre-diagnosis body mass index and survival after breast cancer in the After Breast Cancer Pooling Project

Abstract: Obese and underweight women who develop breast cancer may have poorer survival compared to normal-weight women. However, the optimal weight for best prognosis is still under study. We conducted a prospective investigation of pre-diagnosis body mass index (BMI) and mortality among 14,948 breast cancer patients in the After Breast Cancer Pooling Project. Breast cancer patients diagnosed from 1990-2006 with AJCC Stage I-III breast tumors were drawn from four prospective cohorts. Hazard ratios (HR) and 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
2
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 56 publications
9
67
2
7
Order By: Relevance
“…Several earlier studies have reported that not only obesity but also UW is a negative prognostic indicator in breast cancer [9,[14][15][16]. Some authors have recently demonstrated a relationship between UW and breast cancer subtype with respect to outcome.…”
Section: Discussionmentioning
confidence: 98%
“…Several earlier studies have reported that not only obesity but also UW is a negative prognostic indicator in breast cancer [9,[14][15][16]. Some authors have recently demonstrated a relationship between UW and breast cancer subtype with respect to outcome.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings were similar to Berger, Hertzog, Geary, Fischer, and Farr (2012), who reported that BMI was predictive of psychological functioning among breast cancer survivors. A study by Kwan et al (2011) reported that for breast cancer survivors, the degree of obesity confers a greater risk for survival. In our sample, though the overall sample BMI was 30.06, caution should be taken with the measurement of BMI in some individuals of African ancestry.…”
Section: Discussion Clinical Implications Of the Studymentioning
confidence: 99%
“…15 Obesity is a well-established risk factor for breast cancer incidence and survival, but as described previously, although studies have clearly shown worse mortality with obesity, the association between breast cancer survival and overweight (BMI 25–30) have been less consistent, with some studies showing no adverse effect. 3335 Body mass index only incompletely captures the more relevant physiologic measures of skeletal muscle and adipose tissue.…”
Section: Breast Cancermentioning
confidence: 99%